Uji Daya Hambat Formulasi Salep Ekstrak Etanol Umbi Hati Tanah (Angiopteris sp) terhadap Bakteri Staphylococcus aureus - Rezqi Handayani; Nurul Qamariah (Daun: Jurnal Ilmiah Pertanian dan Kehutanan, 2018)
Hati Tanah tuber (Angiopteris sp) is a plant part that is often used by Dayak tribes in Central Kalimantan as a medicine to heal wounds. This plant is known to contain flavonoid, saponin, tannin and catechol compounds which in previous studies have proven that ethanol extract of this plant can inhibit the growth of Staphylococcus aureus bacteria. Staphylococcus aureus is a Gram-positive bacterium that causes infection in wounds. Some of these strains of bacteria are resistant to available antibiotics. In this study two bases of ointment were used, namely, the bottom of the hydrocarbon ointment and the base of the water-soluble lotion. This study aims to determine the ointment formulation which can inhibit the growth of S. aureus bacteria. Plant extraction is done by the soxhletation method. The inhibitory test in this study uses a process of planting discs that contain active substances as the primary test material. The results showed that the base ointment formulation which could inhibit the growth of Staphylococcus aureus bacteria was an ointment formulation with a water-soluble base.